Pemberdayaan Pewarisan dan Pelatihan Pengelolaan Kuliner Lokal Sagu Pisang kukus (Em Nime Ouw) Orang Ayapo : Empowerment of Heritage and Training for Management of Local Culinary Sago Steamed Banana (Em Nime Ouw) of the Ayapo People - Frank, Simon Abdi K.; Idris, Usman; Flassy, Marlina; Indiarti, Nona Riri; Abisay, Andreas; Yeimo, Selfi (Edujavare Publishing, 2025)
The diversity of Indonesian culinary flavors has become a distinct identity for the region, this local culinary food can be easily found from Sabang to Merauke. This community service activity aims to empower and pass on the skills of managing local culinary arts, namely Steamed Banana Sago (Em Nime Ouw), to the Ayapo community, especially the younger generation. The problem faced is the declining interest of the younger generation in preserving traditional culinary due to the dominance of instant foods and the flow of modernization. The method used in this activity is Participatory Action Research (PAR), with live demonstrations by traditional leaders and elderly women who are still actively involved in making traditional culinary. This activity is carried out in a participatory manner, involving local youth in the entire production process, from selecting ingredients (red sago flour, ripe bananas, coconut water), mixing, wrapping with farofe leaves, to steaming in a traditional stove. The results of the activity show that the demonstrative approach successfully increases practical understanding and cultural awareness among the younger generation, while fostering pride in local culinary identity. In addition, strengthening cultural values through culinary media opens up new economic opportunities based on sustainable local gastronomic tourism.